2001
DOI: 10.1111/j.1151-2916.2001.tb00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hydroxyapatite Lathlike Particles Using High‐Speed Dispersing Equipment

Abstract: Hydroxyapatite lathlike monocrystalline particles were prepared using high-energy dispersing equipment in combination with a pH shock-wave method. The Ca/P atomic ratios were very close to theoretical, and the acidic group content was very small. The particles were nonporous, with anisotropic crystal growth and average grain size ϳ140 -1300 nm in length, ϳ20 -100 nm in width, and ϳ10 -40 nm in thickness. The high-speed dispersing equipment created the proper hydrodynamic conditions for lathlike particle growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Different facets of the crystals have different quantity of the OH − ions and its hindrance effect. If the larger quantity of the OH − will be available at the interface, the hindrance effect of the OH − ions will be stronger on the facets which will affect [22]. To know the role of higher OH − concentration and TiO 2 , various experiments are underway.…”
Section: Resultsmentioning
confidence: 99%
“…Different facets of the crystals have different quantity of the OH − ions and its hindrance effect. If the larger quantity of the OH − will be available at the interface, the hindrance effect of the OH − ions will be stronger on the facets which will affect [22]. To know the role of higher OH − concentration and TiO 2 , various experiments are underway.…”
Section: Resultsmentioning
confidence: 99%
“…Koumoulidis et al [20] reported the synthesis of HA in the form of lath-like monocrystalline particles using the precursors of Ca(H 2 PO 4 ) 2 .H 2 O and CaCl 2 . They employed a highenergy dispersing equipment to synthesize nano HA.…”
Section: Ph Shock Wave Methodsmentioning
confidence: 99%
“…The nanophase HA is therefore perceived to be beneficial in bone tissue engineering as a new generation scaffolding system. There are several methods for the synthesis of nanophase HA, which include wet chemical [14,15] , solid state [16] , hydrothermal [17,18] , mechanochemical [19] , pH shock wave [20] , and microwave processing [21] .…”
Section: Synthesis Of Nanophase Hamentioning
confidence: 99%
“…Various techniques were developed for the synthesis of hydroxyapatites, based on solid state reactions [1,2], chemical precipitation reactions [3][4][5][6][7][8][9][10][11], hydrothermal reactions [12][13][14][15][16][17][18], sol-gel methods [19][20][21][22][23] and mechanochemical methods [24][25][26] using different calcium and phosphorus containing starting materials.…”
Section: Introductionmentioning
confidence: 99%